Effect of body posture on sound absorption by human subjects - Sabbagh, Mostafa; Elkhateeb, Ahmed (Applied acoustics, 2021)
•Sound absorption ability of the human body is affected by the posture.•Standing in well-defined rows exhibits the highest sound absorption.•Carpets increase the equivalent sound absorption area per object.•Heavier clothing increases the equivalent sound absorption area by the body.•Human body is an efficient sound absorber in the mid- and high-frequency bands. In masjid acoustical design, it is important to consider the effects of different human body postures on its sound absorption characteristics. In this study, 15 male subjects were asked to simulate the four Islamic prayer postures (standing, bowing, prostration, and sitting down) to investigate these effects. Additionally, a fifth posture was considered wherein the participants sat down randomly on the floor, simulating the case of worshippers listening to the Friday sermon. Measurements were performed twice in a reverberation room, following ISO 354:2003. The first set of measurements was performed while the participants simulated prayer directly on the bare floor (Setup 1), whereas the second set was performed while prayer was simulated on a carefully selected masjid carpet installed over a polyethylene foam padding (Setup 2). The results confirmed the human subjects’ ability to absorb sound waves in the mid- and high-frequency bands and highlighted the absorption dependence on body posture. In the mid-frequency band for both setups, standing in well-defined rows yielded the highest equivalent sound absorption area per object, AObj (Setup 1 mean = 0.49 m2, Setup 2 mean = 0.70 m2), whereas prostration in well-defined rows yielded the lowest AObj value (Setup 1 mean = 0.34, Setup 2 mean = 0.54 m2). The effects of clothing and carpets on sound absorption by the human body were also revealed. Finally, different approaches for incorporating these findings in acoustic simulation software were discussed.